Learning From The Socio-Religious Integration In Solor Village Indonesia - Irene Ludji; Mariska Lauterboom (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
The Indonesian nation with the motto “Bhineka Tunggal Ika” (Unity in Diversity) is a nation that believes in the beauty of pluralism as the primary model to build unity. Therefore, in building relationships that produce social integration, it should be characterized by acceptance and respect of pluralism and a willingness to learn from this pluralism. Unfortunately, the increasing number of conflicts results in the inability of society to tolerate differences, as seen in the nation’s self-identity becoming unstable. It is clear that the national identity needs to be reinforced through strategic steps that are systematic, clear-cut, and integrated, so that the national unity can be strongly united again. One of the ways to accomplish this is by learning from social integration that occurs in various locations in Indonesia. One such place is in Solor Village, Kupang. In the midst of various conflicts that center on ethnic groups, race, religion, and class issues in Indonesia, the relationship between the indigenous people and newcomers in Solor Village offers an alternative for social integration that can occur in this “Unity in Diversity” nation. This is the focus of this research, which uses a descriptive-qualitative format to analyze social integration strategic issues between newcomers with different religious and cultural backgrounds from the native inhabitants of Solor Village. The research shows that Solor Village residents succeed in building a harmonious life because in facing multiculturalism, religious and cultural values play an important role.Harmonious life in Solor Village confirm that social integration that build on respect to pluralism is possible.